2021
DOI: 10.1016/j.heliyon.2021.e07038
|View full text |Cite
|
Sign up to set email alerts
|

Particle fractionation controls Escherichia coli release from solid manure

Abstract: Bacteria transport through soil is a complex process particularly when the cells are released from solid manures and co-transported with particles. This study focuses on understanding of the Escherichia coli release from different particle fractions (0.25-, 0.5-, 1-, and 2-mm) of solid manure and evaluating different influent boundary conditions during cell release from manure and when a solid manure is applied to the soil. The 0.25-mm and 2-mm particle sizes resulted a greater cell release compared to 0.5-mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The faecal structure will also dictate the speed at which infiltrating water can make contact with resident cells, in turn facilitating their wash-out [11]. The proportion of finer and larger fractions of organic matter that characterises each faecal matrix may also explain differences in mobilisation potential, as has been reported in studies exploring E. coli release from specific fractions of faeces (0.25, 0.5, 1.0, 2.0 mm faecal components) [34]. FIB mobilisation will be influenced by the degree of erodibility associated with the faecal source [11] and observations of faecal disruption during the DESPRAL test identified that dairy faeces more readily disaggregated relative to the goose and deer faeces.…”
Section: Plos Onementioning
confidence: 98%
See 1 more Smart Citation
“…The faecal structure will also dictate the speed at which infiltrating water can make contact with resident cells, in turn facilitating their wash-out [11]. The proportion of finer and larger fractions of organic matter that characterises each faecal matrix may also explain differences in mobilisation potential, as has been reported in studies exploring E. coli release from specific fractions of faeces (0.25, 0.5, 1.0, 2.0 mm faecal components) [34]. FIB mobilisation will be influenced by the degree of erodibility associated with the faecal source [11] and observations of faecal disruption during the DESPRAL test identified that dairy faeces more readily disaggregated relative to the goose and deer faeces.…”
Section: Plos Onementioning
confidence: 98%
“…We did not determine how FIB mobilisation varied over the duration of the 'event'. Over longer experimental timeframes and using different measures of mobilisation there are reports of a faster, or in some cases more irregular, initial FIB release from faeces followed by a slower steady-state FIB release [34,37]. Despite a smaller mass of faeces being used in assessing FIB mobilisation from goose faeces, the ratio of faecal mass to rainwater was consistent with that used to determine FIB concentrations released from dairy cow and deer faeces, and thus the difference in faecal mass should not impact on comparing the concentrations of FIB mobilised across different treatments.…”
Section: Plos Onementioning
confidence: 99%